Basis for prokaryotic specificity of action of aminoglycoside antibiotics. - Recht, M I (1999)
The aminoglycosides, a group of structurally related antibiotics, bind to rRNA in the small subunit of the prokaryotic ribosome. Most aminoglycosides are inactive or weakly active against eukaryotic ribosomes. A major difference in the binding site for these antibiotics between prokaryotic and eukaryotic ribosomes is the identity of the nucleotide at position 1408 (Escherichia coli numbering), which is an adenosine in prokaryotic ribosomes and a guanosine in eukaryotic ribosomes. Expression in E.coli of plasmid-encoded 16S rRNA containing an A1408 to G substitution confers resistance to a subclass of the aminoglycoside antibiotics that contain a 6' amino group on ring I. Chemical footprinting experiments indicate that resistance arises from the lower affinity of the drug for the eukaryotic rRNA sequence. The 1408G ribosomes are resistant to the same subclass of aminoglycosides as previously observed both for eukaryotic ribosomes and bacterial ribosomes containing a methylation at the N1 position of A1408. The results indicate that the identity of the nucleotide at position 1408 is a major determinant of specificity of aminoglycoside action, and agree with prior structural studies of aminoglycoside-rRNA complexes.